PENGARUH RETURN SAHAM, MARKET VALUE, DAN RETURN ON ASSETS TERHADAP HOLDING PERIODE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Kusumawaty, Afrillia Frida; Sulistyo, Sulistyo; halim, abdul (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2016)
Objective test singer is to review and explain: 1) the effect of partial differences operate against the holding period return under common control manufacturing company the listing on the stock exchange; 2) the effect of partial differences operates holding period against the market value of manufacturing the listing on the stock exchange; 3) the effect of partial differences operates holding period return on assets against manufacturing company the listing on the stock exchange; 4) The influential variables railing against big holding period the list manufacturing company in BEI.Used operates research is explanatory research, ie to explain the causal relationship between research variables through hypothesis testing (Singarimbun and Effendy, 2012). Singer study using a quantitative approach, is an variable the values stated hearts form numbers (Sugiyono, 2012). These variables under common control is returned, market value, return on assets and holding period. The use of secondary data research singer Â hearts through internet akses www.idx.co.id to, form finance and manufacturing company under common closing price the listing on the stock exchange year 2014-2015, then analyzed with linear regression. To review test the hypothesis using t-test.Results singer prove that: 1) Variable X1 = return under common control effect against holding period. It singer indicated by the t-test of significance value of 0.000 small moreÂ from negligent 0.05. While the value of regression coefficient of 4.221 is positive, it means if return same, then holding period increased also; 2) Variable X2 = value markert effect against holding period. It Singer indicated by the t-test of significance value of 0.026 Small more from negligent 0.05. While the value of regression coefficient of 1.030 is positive, it means that if the value markert increased also then holding period; 3) Variable X3 = return on assets effect against holding period. It singer indicated by the t-test of significance value of 0.010 small more from negligent 0.05. While the value of regression coefficient of 3.131 is positive, it means if return on assets increased also then the holding period; 5) Variable X1 = return under common effect against big fence holding period. It singer indicated by coefficient regression t-test of differences of variables X1 = return under common control amounting to 4.221 indicates more big from values regression coefficient t-test of differences X2 = market value of 1,030 and of values regression coefficient t-test of differences X3 = back on 3. assets amounted to 131.